CEO social capital and implied cost of capital: Based on the empirical evidence of Chinese family businesses - Ya Qi; Ying Zou; Fuan Shi (PLoS ONE, 2025)
Social capital plays a crucial role in resource integration within Chinese family businesses. This research investigates the relationship between CEO social capital and the implied cost of capital, while also considering the influence of CEO type on this relationship. The empirical results based on China’s A-share family-listed companies show that CEO social capital helps to reduce the implied capital cost of family business. However, compared with non-family CEO, the effect of family CEO social capital on reducing the implied cost of capital is weaker. The mechanism analysis confirms that CEO social capital reduces the implied cost of capital through reducing corporate risk and improving information transparency. The heterogeneity analysis reveals that CEO social capital significantly reduces the implicit cost of capital only in entrepreneurial families, companies with low family control, and those without intergenerational transmission. Additionally, the effect of CEO social capital is more pronounced in fiercely competitive markets and high-tech industries. When economic policy uncertainty is high and investor legal protections are weak, CEO social capital can better exert its complementary effect on formal institutions. These findings not only provide a theoretical foundation for leveraging the informal system of social capital to strengthen family governance but also offer practical insights for addressing the classic decision of whether to choose family succession or hire professional managers.